1981
DOI: 10.1073/pnas.78.8.4946
|View full text |Cite
|
Sign up to set email alerts
|

Xenon NMR: chemical shifts of a general anesthetic in common solvents, proteins, and membranes.

Abstract: The rare gas xenon contains two NMR-sensitive isotopes in high natural abundance. The nuclide '"Xe has a spin of 'h; '31Xe is quadrupolar with a spin of 3/2. The complementary NMR characteristics ofthese nuclei provide a unique opportunity for probing their environment. The method is widely applicable because xenon interacts with a useful range of condensed phases including pure liquids, protein solutions, and suspensions of lipid and biological membranes. Although xenon is chemically inert, it does interact w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(136 citation statements)
references
References 11 publications
5
131
0
Order By: Relevance
“…These earlier studies suggested the following peak assignments: 187.2 ppm, muscle 19, 20, 21; 192.7 ppm, white matter (and soft‐tissue in this study) 18, 19, 20, 21; 195.6 ppm, gray matter 18, 19, 20, 21; 199.6 ppm, aqueous solution (cerebrospinal fluid, plasma, and interstitial fluid in this study) 10, 11, 24, 25, 26 and fat/lipid tissue outside the brain 19, 20; and 217.2 ppm, red blood cells 4, 10, 24, 26.…”
Section: Discussionsupporting
confidence: 65%
“…These earlier studies suggested the following peak assignments: 187.2 ppm, muscle 19, 20, 21; 192.7 ppm, white matter (and soft‐tissue in this study) 18, 19, 20, 21; 195.6 ppm, gray matter 18, 19, 20, 21; 199.6 ppm, aqueous solution (cerebrospinal fluid, plasma, and interstitial fluid in this study) 10, 11, 24, 25, 26 and fat/lipid tissue outside the brain 19, 20; and 217.2 ppm, red blood cells 4, 10, 24, 26.…”
Section: Discussionsupporting
confidence: 65%
“…[35][36][37] Recently, extensive reviews regarding the history and development of hyperpolarized xenon NMR have been published. 38,39 Biological systems studied with 129 Xe NMR include globular proteins such as myoglobin and hemoglobin, [40][41][42][43][44][45][46] membrane associated peptides such as gramicidin, 47 and lipid membranes themselves. 48 While xenon shows appreciable binding to many proteins, as evidenced by its use in making heavy atom derivatives of protein crystals for x-ray crystallography, 49 In spite of the favorable attributes of xenon interacting with proteins in solution, high-sensitivity molecular sensing is not compatible with the fast-exchange characteristic of xenon-protein interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, xenon's relatively high solubility in biological tissues (2), along with its exquisite sensitivity to its environment that results in an enormous range of chemical shifts upon solution (3), make hyperpolarized Xe129 particularly attractive for exploring certain characteristics of lung function, such as gas exchange and uptake (4,5), not accessible with the use of hyperpolarized He3. Upon inhalation, Xe129 gives rise to multiple MRI spectral peaks in the lung (6)(7)(8)(9), each associated with a physically different compartment.…”
mentioning
confidence: 99%